Method of specifying aqueous dispersions of polytetrafluoroethylene (PTFE) materials (BSI, 1991)
Polytetrafluoroethylene, Thermoplastic polymers, Plastics, Aqueous dispersions, Dispersions (chemical), Designations, Marking, Gravimetric analysis, Evaporation residue determination, Volatile matter determination, Testing conditions, Density measurement, pH measurement, Viscosity measurement, Safety measures, Chemical composition, Determination of content, Surfactants